The Cognitive Value of Hallucinations - Sikora, Tomasz (Studia religiologica, 2015)
With beginnings probably dating back to the end of the Middle Palaeolithic period, shamanism seems to be predominantly connected with the use of hallucinogenic agents and the experiences resulting therefrom. For this reason it is worth asking how the shamanistic cultural complex could function over such a long period of time in adaptive terms if the substance of its practice and ideol-ogy included the processing of information based on hallucinations. In the light of contemporary nomenclature, the latter are understood as inadequate erroneous perceptions. Accepting such a con-cept of hallucinations, it is possible to explain the long currency of shamanism on the basis of evo-lutionary cognitive error management theory, costly signalling theory, or evolutionary psychiatric group-splitting theory. However, the dominant approach to the phenomenon of hallucination may be questioned, and it is conceivable that at least some of its contents constitute a mediated projec-tion of subliminal percepts preceding an experience of hallucinations or co-occurring with them. Transformations of hallucinations preceding their entry to the field of consciousness may be gov-erned by the rules of association described by Herbert Silberer’s theory of self-symbolisation and those brought to light by such researchers on subliminal perception as Otto Pötzl, Charles Fisher, or Norman Dixon. From this new perspective, a new definition of hallucination must be developed – a definition that will take the actual cognitive value of this phenomenon into consideration and be more adequate for providing a description of the full cognitive dynamics of the shamanistic complex.